Factors associated with oncology patients' involvement in shared decision making during chemotherapy. Issue 11 (5th October 2016) - Colley, Alexis; Halpern, Jodi; Paul, Steven; Micco, Guy; Lahiff, Maureen; Wright, Fay; Levine, Jon D.; Mastick, Judy; Hammer, Marilyn J.; Miaskowski, Christine; Dunn, Laura B.
Abstract: Objective: Oncology patients are increasingly encouraged to play an active role in treatment decision making. While previous studies have evaluated relationships between demographic characteristics and decision‐making roles, less is known about the association of symptoms and psychological adjustment characteristics (eg, coping styles and personality traits) and decision‐making roles. Methods: As part of a larger study of symptom clusters, patients (n = 765) receiving chemotherapy for breast, gastrointestinal, gynecological, or lung cancer provided information on demographic, clinical, symptom, and psychological adjustment characteristics. Patient‐reported treatment decision‐making roles (ie, preferred role and role actually played) were assessed using the Control Preferences Scale. Differences among patients, who were classified as passive, collaborative, or active, were evaluated using χ 2 analyses and analyses of variance. Results: Over half (56.3%) of the patients reported that they both preferred and actually played a collaborative role. Among those patients with concordant roles, those who were older, those with less education and lower income, and those who were less resilient were more likely to prefer a passive role. Several psychological adjustment characteristics were associated with decision‐making role, including coping style, personality, and fatalism. Conclusions: Oncology patients' preferences for involvement in treatment decision making are associated with demographic characteristics as well as with symptoms and psychological adjustment characteristics, such as coping style and personality. These results reaffirm the complexities of predicting patients' preferences for involvement in decision making. Further study is needed to determine if role or coping style may be influenced by interventions designed to teach adaptive coping skills.